Said Nursi's Thoughts and Its Contribution in Mainstreaming Moderation at Islamic Higher Education in Indonesia - Faiz, Muhammad (IAIN Syekh Nurjati Cirebon, 2023)
This research focuses on the study of the spectrum of Said Nursi’s thought who became an important figure in the dynamics of Islam in Turkiye during the transitional period leading up to the collapse of the Ottoman Caliphate and the founding of the Republic of Turkiye. Said Nursi with the cultural movement